Multi‐Mechanism Collaborative Bionic Fixation Technique Between a Wide Range of Solid Interfaces - Shixun Fu; Jun Sun; Zhiyong Hu; Yongjin Zhao; Tianchang Yao; Xipeng Wang; Yuanming Ji; Kai Deng; Keju Ji (Advanced Science)
Abstract For rough surfaces, stable, fast, and repeatable fixation has wide applicability in transportation, fire protection, and other fields. Different rough surfaces present technical challenges for achieving convenient and reliable fixation. Based on the highly adhesive attachment structures of typical organisms, a multi‐mechanism (negative pressure adsorption, mechanical locking, and chemical bonding) cooperative bionic fixation device is proposed. The device is equipped with a suction disc with gradient guide channels, a microneedles friction‐enhancing unit, and fast‐curable UV glue. These components work together to complete the fixation. The detachment work (max. 5.7 and 5.5 J) and pull‐off force (max. 377 and 175 N) are evaluated on sandpaper of different roughness under vertical and horizontal pulling respectively. By analyzing the detachment process and experimental curves, the cooperative principle of the multi‐mechanism is identified. In addition, the microneedles with soft backing at the bionic fixation device bottom improve its adaptability to rough surfaces. The gradient guide channels of the suction disc create Laplace pressure to speed up the UV glue flow and shorten fixation time. Furthermore, its applicability is demonstrated by combining it with monitoring equipment and an adult to attach to rough surfaces.